SEASONAL CHANGES IN THE BIOCHEMICAL COMPOSITION OF A HILLSTREAM FISH GARRA MULLYA (SYKES) - Somvanshi, V S (Indian Journal of Fisheries, 2011)
In the hillstream fish Garra Mullya (Sykes) marked seasonal variations in phosphorus, water, fat, protein and glycogen were observed during a one-year study. The fat and water contents were inversely related; maximum fat was observed during the prespawning months, while the minimum after the breeding. The relationship between fat and protein was a direct one. The muscle glycogen was in assocation to feeding and spawning activity. High energy values were found throughout the prespawning period.